Klotho protein syntesis inductors cardio protective effect in experimental acute myocardial infarction - Pavlov, S. V.; Nikitchenko, J. V.; Robota, D. V.; Павлов, Сергій Васильович; Нікітченко, Юлія Вікторівна; Робота, Дмитро Вадимович (Запорізький державний медичний університет, 2022)
Recent decades have been marked with a global steady growing trend towards an increase in the incidence of vascular diseases linked to the general population aging, and the increasing incidence rate of diabetes mellitus, arterial hypertension and atherosclerosis.
Keywords: тези доповідей